Web Results

SOLUTION: How do I simplify 2a^2b^3(4a^2+3ab^2-ab)? - Algebra

www.algebra.com/algebra/homework/Functions/Functions.faq.question.174839.html

SOLUTION: How do I simplify 2a^2b^3(4a^2+3ab^2-ab)?. Algebra -> Functions - > SOLUTION: How do I simplify 2a^2b^3(4a^2+3ab^2-ab)? Log On ...

can someone help me simplify 2a^2b^3(4a^2+3ab^2-ab) - Jiskha ...

www.jiskha.com/search/index.cgi?query=can someone help me simplify 2a^2b^3(4a^2+3ab^2-ab)=?

If 3ab=6, what is the value of a in terms of b? a. 2 b. 2/b c. 2b^2 d. 2b e. 2b^2 My ... Simplify 2a^2 b^3 (4a^2 + 3ab -ab) A.) 8a^4 b^5 + 3a^3 b^5 - 2a^3 b^4 B.) ...

(2a + 6 * 2)(3a + 3) - Simplifying Expressions Calculator -- Algebra ...

www.algebrahelp.com/calculators/expression/oops/calc.do?expression=(2a + 6 * 2)(3a + 3) + a

Simplifying (2a + 6 * 2)(3a + 3) + a Multiply 6 * 2 (2a + 12)(3a + 3) + a Reorder the terms: (12 + 2a)(3a + 3) + a Reorder the terms: (12 + 2a)(3 + 3a) + a Multiply ...

(3a 2 + 6a) Reorder the terms - Simplifying Expressions Calculator ...

www.algebrahelp.com/calculators/expression/oops/calc.do?expression=2(a^2 + a)(3a^2 + 6a)

Simplifying 2(a<sup>2</sup> + a)(3a<sup>2</sup> + 6a) Reorder the terms: 2(a + a<sup>2</sup>)(3a<sup>2</sup> + 6a) ... 3a<sup>3</sup> + 6a<sup>3</sup> = 9a<sup>3</sup> 2(6a<sup>2</sup> + 9a<sup>3</sup> + 3a<sup>4</sup>) (6a<sup>2</sup> * 2 + 9a<sup>3</sup> * 2 + 3a<sup>4</sup> * 2) (12a<sup>2</sup> + 18a<sup>3</sup> + 6a<sup>4</sup>).

Answers (easy read)

www.bbk.ac.uk/mybirkbeck/get-ahead-stay-ahead/maths/01_Algebra_1_answers_easy_read.pdf

Notice that 10) is a bit of a trick question as it cannot be simplified. B) 4a2 + 2b – 7a +3b + 8b – 9 (a – 2) + 18. 1) List all ... 1) 2a + 3a = 2 (7) + 3(7) = 14 + 21 = 35. 2) 7a ... 11) 3a(b – a2) – a2(2 – 3a) = 3ab – 3a3 – 2a2 + 3a3 =3ab – 2a2. 12) ... 8) 4 = b +2y ; b + 2y = 4 ; b = 2y – 4. 9). ; b = 4a. 10). ; 4 = 2ab ; 2ab = 4 ;....

How do I Simplify (2a+2b) ^2+ (2a-2b) ^2? - Quora

www.quora.com/How-do-I-Simplify-2a 2b-2 -2a-2b-2

It is very simple, take a look at the steps below. Let's simplify step-by-step. ... How do I simplify (( (2a^3b) ^3)-2a^2) / (4a^5b^3)? · How do I factor ... + B^2 + 2AB

Simplify 4a^3b^2+2a^2b^2+3ab/ab Tiger Algebra Solver

www.tiger-algebra.com/drill/4a~3b~2_2a~2b~2_3ab/ab/

Equation at the end of step 1 : b (((4•(a<sup>3</sup>))•(b<sup>2</sup>))+((2•(a<sup>2</sup>))•(b<sup>2</sup>)))+((3a•—)•b) a. Step 2 : Equation at the end of step 2 : (((4•(a<sup>3</sup>))•(b<sup>2</sup>))+(2a<sup>2</sup>•b<sup>2</sup>))+3b<sup>2</sup>. Step 3 : ...

Rational Expressions Assignments - 2, Rational Expressions Solutions

www.math10.com/en/algebra/rational-expressions-assignments-2.html

(a<sup>2</sup> + 2ab + b<sup>2</sup> - a<sup>2</sup> + 2ab - b<sup>2</sup>) = (2a<sup>2</sup> + 2b<sup>2</sup>)(4ab) = 2(a<sup>2</sup> + b<sup>2</sup>).4ab = 8ab(a<sup>2</sup> + b <sup>2</sup>). Assignment 19 Simplify the following expression: ... B) (2a + 5)<sup>2</sup> – 5(4a + 5) = ( 2a)<sup>2</sup> + 2.2a.5 + 5<sup>2</sup> – 5.4a – 5.5 = 4a<sup>2</sup> + 20a + 25 ... B) (a - b)<sup>3</sup> = a<sup>3</sup> - 3a<sup>2</sup>.b + 3a.b <sup>2</sup> - b<sup>3</sup> = a<sup>3</sup> - 3ab(a - b) - b<sup>3</sup> C) (x - a)(x - b) = xx - xb - ax + ...

CHAPTER 9 BASIC ALGEBRA

documents.routledge-interactive.s3.amazonaws.com/9780415662840/answers/UEM_Sol_to_Exerc_Chap_009.pdf

2a – a + 5b – 3b + 7c – 3c = a + 2b + 4c. 3. Simplify. 2. 2. 2 3. 7. 4. 2. x x. y x .... +. 12. Simplify 3a ÷ 9ab. 3a ÷ 9ab. 3. 9 a ab. ≡. = 1. 3b. 13. Simplify 4a. 2 b ÷ 2a ...

Algebraic expressions, Simplifying algebraic expressions ... - Nabla.hr

www.nabla.hr/SP-SolvedProblemsU01.htm

Solutions: a) - 4a<sup>3</sup> + 3a<sup>2</sup> + 5a<sup>3</sup> - 7a<sup>2</sup> = (- 4 + 5) · a<sup>3</sup> + (3 - 7) · a<sup>2</sup> = a<sup>3</sup> - 4a<sup>2</sup>,. b) (x <sup>2</sup> - x + 1) ... a<sup>3</sup> - 2a<sup>2</sup>b + ab<sup>2</sup> - a<sup>2</sup>b + 2ab<sup>2</sup> - b<sup>3</sup> = a<sup>3</sup> - 3a<sup>2</sup>b + 3ab<sup>2</sup> - b<sup>3</sup>,. b) (x - 2)<sup>3</sup> ... d) 5ab<sup>2</sup> - 3a<sup>3</sup> - 10b<sup>3</sup> + 6a<sup>2</sup>b = 5b<sup>...